Curcumin plays a local anti‐inflammatory and antioxidant role via the HMGB1/TLR4/NF‐ΚB pathway in rat masseter muscle under psychological stress. (13th December 2021) - Miao, Li; Huang, Fei; Sun, Ying‐Ying; Jiang, Wei; Chen, Yong‐Jin; Zhang, Min
Abstract: Background and objective: Psychological stress causes structural and metabolic dysfunction of masseter muscles. The anti‐inflammatory and anti‐oxidative polyphenol curcumin plays a local antioxidant role in rat masseter muscles under psychological stress by an as‐yet‐unknown mechanism. The present study aimed to assess curcumin anti‐inflammatory and anti‐oxidative effects on masseter muscle and its possible molecular mechanisms. Methods: We constructed a rat model of chronic unpredictable moderate stress (CUMS). Psychological stress was assessed by determining the levels of adrenocorticotropic hormone (ACTH) and cortisol in serum. Enzyme‐linked immunosorbent assays measured inflammatory cytokines and markers of oxidative stress in masseter muscles. Levels of high‐mobility group box 1 (HMGB1), interleukin (IL)‐1β, IL‐6 and tumour necrosis factor‐alpha (TNF‐α) were determined using quantitative PCR analyses and immunofluorescent staining. Toll‐like receptor 4 (TLR4) and nuclear factor kappa B (NF‐κB) activation were examined using western blotting. Results: The CUMS group showed increased serum cortisol and ACTH levels. Pathological changes in the ultrastructure, oxidative stress and inflammatory cytokines in the masseter muscles were also observed. Curcumin treatment (50, 100 mg/kg) ameliorated these changes significantly by varying degrees. Mechanistically, increased levels of phosphorylated NF‐κB, toll‐like receptor 4 and HMGB1 were observed, which were also ameliorated by curcumin treatment. Conclusion: Curcumin can reduce local pathological changes, levels of oxidative stress and inflammatory factors in masseter muscles. Psychological stress activates HMGB1 expression and increases the expression of downstream TLR4 and p‐NF‐κB, which could be reduced by curcumin. Thus, curcumin might exert anti‐inflammatory and antioxidant effects in masseter muscles via the HMGB1/TLR4/NF‐κB pathway.